Natural Vibration Frequencies of Flexible Rotor Blades: A Method Based on Consideration of Perfectly Flexible Blades - Lockwood Taylor, J. (Aircraft Engineering and Aerospace Technology, 1958)
HELICOPTER rotor blades, as is well known, are subjected to alternating bending stresses at various multiples of the rotor r.p.m. when the aircraft is flying forward. One of the factors determining the magnitude of the fluctuating stresses at the various frequencies is the approach to resonance between the harmonic components of the periodically varying aerodynamic loads and the natural blade frequencies. Most rotor blades are flexible enough to allow the frequencies of at any rate the lower modes, which are probably the most important, to be estimated by applying a correction for blade bending stiffness to the natural frequency of the blade if it were perfectly flexible, and subject only to inertia and centrifugal forces. It is on this latter aspect of the problem that the present article is concentrated.